2019
DOI: 10.1101/601633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacillus subtilis ALBA01 can mitigate onion pink root symptoms caused by Setophoma terrestris

Abstract: 21Soil-borne pathogen Setophoma terrestris is the causal agent of pink root of onion, one 22 of the most challenging diseases in onion production. Conventional approaches for 23 managing the disease like solarization, soil fumigation and crop rotation have not been 24 proven effective enough. In this work, we evaluated the biocontrol capacity of Bacillus 25 subtilis ALBA01 (BsA01) against S. terrestris, in a highly susceptible onion cultivar, both 26 under greenhouse and field conditions. Disease incidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Bacillus as a biocontrol agent can produce antimicrobial compounds. Recently, the bacterium Bacillus subtilis (strain ALBA01) acted as a biocontrol agent against the fungus P. terrestris under both greenhouse and field conditions (Sayago et al 2019), where the findings of this study noticeably indicated important biological protection expressed by B. subtilis against the soil-borne P. terrestris fungus. P. terrestris diseased plants inoculated with the bacterium showed usual development, particularly the photosynthetic activity; thus the strain ALBA01 of the B. subtilis bacteria may be employed to decrease the damage on the pink root (Sayago et al 2019).…”
Section: Biological Controlmentioning
confidence: 68%
“…Bacillus as a biocontrol agent can produce antimicrobial compounds. Recently, the bacterium Bacillus subtilis (strain ALBA01) acted as a biocontrol agent against the fungus P. terrestris under both greenhouse and field conditions (Sayago et al 2019), where the findings of this study noticeably indicated important biological protection expressed by B. subtilis against the soil-borne P. terrestris fungus. P. terrestris diseased plants inoculated with the bacterium showed usual development, particularly the photosynthetic activity; thus the strain ALBA01 of the B. subtilis bacteria may be employed to decrease the damage on the pink root (Sayago et al 2019).…”
Section: Biological Controlmentioning
confidence: 68%